Analysis of Student Satisfaction with the Quality of Education Services and Lecturer Performance Using the Survey and Naive Bayes Methods - Syefudin Syefudin; Hendry Hendry; Ade Iriani (Postgraduate, University of Mataram, 2023)
This research aims to evaluate the level of student satisfaction with the quality of educational services and the assessment of faculty performance at STMIK Tegal through a survey method and the application of Naive Bayes. The research sample consists of 100 active students from different study programs. Survey results were processed using the Naive Bayes method to assess the impact of variables related to the quality of educational services and faculty performance on the level of student satisfaction. The findings of the analysis indicate that the quality of educational services has a positive effect on student satisfaction, while faculty performance also contributes positively. This research has practical implications for improving the quality of educational services and faculty performance at STMIK Tegal. Infrastructure and facilities supporting the teaching and learning process can be enhanced, and faculty members can receive training and guidance to improve their teaching quality. In the long term, this can enhance the institution's reputation and overall student satisfaction. This study has limitations related to the limited sample size and the use of non-random sampling techniques. Therefore, future research can expand the sample size and use more representative sampling techniques to enhance the accuracy of research results